Uncertainty about QE effects when an interest rate peg is anticipated - Rafael Gerke; Sebastian Giesen; Daniel Kienzler (Deutsche Bundesbank, 2018)
After hitting the lower bound on interest rates, the Eurosystem engaged in a public sector purchase programme (PSPP) and forward guidance (FG). We use prior and posterior predictive analysis to evaluate the importance of parameter uncertainty in an analysis of these policies. We model FG as an anticipated temporary interest rate peg. The degree of parameter uncertainty is considerable and increasing in the length of FG. The probability of being able to reset prices and wages is the most important factor driving uncertainty about inflation. In contrast, variations in financial intermediaries' net worth adjustment costs have little impact on in ation outcomes.
Keywords: C53; E32; E52; 330; prior/posterior predictive analysis; anticipated interest rate peg; parameter uncertainty; euro area; QE; PSPP; forward guidance puzzle